Adequate Nutritional Intake and Nutritional Status with Adolescent Menstrual Cycle - Davidson, Sarah Melati; Dampang, Damelya Patricksia; Padjao, Alfrilin (Sarana Ilmu Indonesia (salnesia), 2023)
Menstrual cycle disorders can often occur in teenagers and have the potential to affect their reproductive health. Several studies have indicated that adequate nutrition is linked to menstrual cycle disorders. The purpose of this study was to identify the profile of adolescent girls and analyze the relationship between their level of energy intake, macronutrients (protein, lipid, and carbohydrates), micro-nutrients (vitamin C, magnesium, and iron), and also nutritional status with menstrual cycle. The study was conducted from January to April 2022 at Lentera Harapan High School in Palopo City. An analytic survey research design with a cross-sectional approach was used, and the research sample consisted of 66 respondents selected using purposive sampling technique. Data analysis was analyzed using chi-square test. The results showed that 57,6% of the subjects had menstrual cycle disorders with most of the respondents having normal nutritional status. The study also showed a high variety of energy, macro-nutrient, and micro-nutrient consumption. However, the average intake of energy, carbohydrates, vitamin C, magnesium, and iron did not meet daily requirements. Nutritional status was significantly related to menstrual cycle (p-value<0,05). Energy, protein, lipid, carbohydrates, and iron intake were also significantly correlated to menstrual cycle (p-value<0,05). There was no relationship between adequate intake of vitamin C and magnesium with menstrual cycle (p-value>0,05). It is recommended that adolescent girls receive education about balanced nutrition and related nutrients to help reduce complaints during menstruation and reduce menstrual cycle disorders.